(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Fetal blood flow through the umbilical cord vessels associated with abnormal coiling of the cord can have serious deleterious effects on the health of the fetus and newborn. Matrix metallopeptidase-9 (MMP-9) is a class of enzymes that are involved in the degradation of the extracellular matrix collagen and other proteins. Objective: To investigate the profile of MMP-9 immunohistochemical reactivity in the umbilical cord with variable coiling indices. Methods: In this study, 60 umbilical cords with inclusion criteria (full term newborns with normal perinatal outcome whose mothers were normal) collected from labor rooms of Ibn Al-Balady Hospital in Baghdad. The cords were used for immunohistochemistry matrix metaloprotenase-9 study. Results: The results of Immunohistochemical study showed variability in mesenchymal tissue reactivity among the three groups of the umbilical cords in different regions (sub amniotic region, perivascular region and central region) of the umbilical cords. The results obtained were evaluated by using the Aprio image scope analysis software. Conclusion: The immunohistochemical reactivity could indicate that the MMP-9 localization has role in degradation of collagen and proteins to maintain a harmless perivascular pressure in association with hypercoiling and hypocoiling of the cord and that could preserve the normal vascular blood flow to a certain limit. Keywords: Umbilical cords, human, coiling index, matrix metalloprotienase-9, normal pregnancy, immunohitochemistry. Citation: Hiba A. Abdul Sattar, Hayder J. Mubarak. The profile of matrix metalloproteinase-9 in relation to coiling index of human umbilical cord. Iraqi JMS. 2017; Vol. 15(2): 165-174 . doi: 10.22578/IJMS.15.2.9